Prevalence of intestinal helminths in stray dogs of Kalar city / Sulaimani province - Bajalan, Mariwan Musa Muhammad (The Iraqi Journal of Veterinary Medicine, 2010)
A total of 50 stray dogs, 26 males and 24 females from 3 different areas in Kalar city were killed and autopsied during the period from October 2005 till end of March 2006.The overall infection rates with cestodes and nematodes were 84% and 36%, respectively. No trematodes and acanthacephalans were found in the intestine of the dogs.The rate of infection was 75% in area around abattoir, 92.85% in areas of the periphery of Kalar and 95% in the city center.The following cestodes were identified: Taenia spp. (78%), Dipylidium caninum (26%), Diphylobothrium latum (2%) and Mesocestoides sp. (2%). Only two intestinal nematodes, Toxocara sp. and Ancylostoma caninum were recovered with prevalence rates of 36% and 2%, respectively.